Impact of Asian ethnicity on outcome in metastatic EGFR‐mutant non–small cell lung cancer. Issue 6 (4th September 2019) - Gibson, Amanda J. W.; D'Silva, Adrijana; Elegbede, Anifat A.; Tudor, Roxana A.; Dean, Michelle L.; Bebb, Dafydd Gwyn; Hao, Desiree
Abstract: Aim: To determine factors associated with survival in de novo stage IV, non–small cell lung cancer (NSCLC) patients possessing epidermal growth factor receptor mutations (EGFRmut + ) receiving tyrosine kinase inhibitors (TKI) in the first‐line setting. Methods: The Glans‐Look Lung Cancer Database was used to retrospectively review stage IV EGFRmut + NSCLC patients diagnosed 2010–2016 receiving first‐line TKI. Patients with overall survival times in the upper quartile (≥34 months) were designated "long‐term survivors" (LTS), the remaining deemed "average‐term survivors" and characteristics between these groups were compared in univariate analysis, and multivariable models constructed to determine predictors of outcome. Results: Of 170 eligible patients, median overall survival was 21 months. LTS were significantly more likely to be of Asian ethnicity, be never‐smokers and not possess brain or bone metastases at diagnosis. Asian and non‐Asian patients were comparable, save for an increased propensity of Asian patients to be never smokers and have normal‐range BMI. Multivariable analysis revealed Asian ethnicity [hazard ratio (HR) = 0.65; P  = 0.016] and never‐smoking history (HR = 0.65; P  = 0.034) as indicators of improved outcome, and presence of brain metastasis at diagnosis an indicator of poor outcome (HR = 2.21; P  < 0.001). Conclusions: Analysis of this population‐based cohort identifies never‐smoking history and absence of brain metastasis along with Asian ethnicity as an independent prognosticators of favorable outcome, and reveals Asian patients to be clinicopathologically similar to non‐Asian patients. These findings suggest Asian patients represent a unique subpopulation within EGFRmut + NSCLC who may possess different biological underpinnings of NSCLC.